Corrigendum to “Layered double hydroxides as effective carrier for anticancer drugs and tailoring of release rate through interlayer anions” [Journal of Controlled Release 224 (2106) 186–198] (Layered double hydroxides as effective carrier for anticancer drugs and tailoring of release rate through interlayer anions (2016) 224 (186–198), (S016836591630013X), (10.1016/j.jconrel.2016.01.016)) - Senapati S.; Thakur R.; Verma S.P.; Duggal S.; Mishra D.P.; Das P.; Shripathi T.; Kumar M.; Rana D.; Maiti P. (My University, 2025)
The authors regret that the initial published version of this article an error in the assembly of Fig. 7b resulted in some image duplications. The corrected Fig. 7b includes the correct images of the experiment. This correction/omission doesn't alter any conclusion of the article as quantitative analysis of the experiment has been performed through MTT assay, presented in Fig. 7a. [Figure Presented] The figure legend remains the same. The corrections made in this corrigendum do not affect the original conclusions of the article. The author's apologies for any inconvenience caused. © 2016 Elsevier B.V.